2021
DOI: 10.3390/ijerph18073703
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dietary Patterns and Cardiovascular Disease Risk in Korean Older Adults

Abstract: Objectives: The purpose of this study was to assess the relationship between dietary patterns and the 10-year risk of cardiovascular disease (CVD) in the elderly population in Korea. Methods: Cluster analysis was conducted on the data of 1687 elderly participants (797 men and 890 women) aged ≥ 65 years from the 2014–2016 Korea National Health and Nutrition Examination Survey (KNHANES), using a 24-hour dietary recall survey to assess dietary patterns. Dietary patterns were classified into clusters 1 (typical Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that the differences in dietary patterns and their occurrence may be explained by the region of residence [18,20], both due to its cultural specificity and economic characteristics. In the study of Czarnoci ńska et al [41], carried out in Polish young women, it was shown that women from more affluent regions represented the pattern characterized by a high consumption of vegetables and fruit more often, while a high consumption of fast food and sweets was characteristic of poorer regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the differences in dietary patterns and their occurrence may be explained by the region of residence [18,20], both due to its cultural specificity and economic characteristics. In the study of Czarnoci ńska et al [41], carried out in Polish young women, it was shown that women from more affluent regions represented the pattern characterized by a high consumption of vegetables and fruit more often, while a high consumption of fast food and sweets was characteristic of poorer regions.…”
Section: Discussionmentioning
confidence: 99%
“…The "traditional" DP was also often distinguished, i.e., dietary pattern specific for the country in which the research is conducted [11,12]; for example, the "traditional Polish" DP usually consists of potatoes, meat, vegetables, cheese, animal fats, and sugar, which are foods typical of traditional Polish cuisine [12]. Up until now, studies have distinguished dietary patterns among the elderly that are more beneficial to health, such as "prudent", "healthy", or "Mediterranean", those that are more detrimental to health, i.e., "western" or "unhealthy" DPs [13][14][15][16][17], as well as a "traditional" dietary pattern [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…Macronutrients (carbohydrates, fat, and proteins) play an important role in preventing muscle loss and IR in aging muscle biology ( 17 19 ). A healthy and balanced diet rich in vegetables, fruits, legumes, and fish is associated with a lower 10-year risk of incidence of CVDs than the typical white rice and grain-based Korean diet in elderly people ( 20 ). The recent Korean National Health and Nutrition Examinations Survey (KNHANES) reported that excessive carbohydrate, low fruit, and imbalanced food and nutrient intakes contribute to cardiometabolic abnormalities in rural residents ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…A healthy and Abbreviations: AWGS, Asian Working Group for Sarcopenia; ASM, appendicular skeletal muscle mass; BIA, bioelectrical impedance analysis; BMI, body mass index; BP, blood pressure; CI, confidence interval; CM cardiometabolic multimorbidity; CVD, cardiovascular disease; FA, fatty acid; HDL, high-density lipoprotein; IR, insulin resistance; KDRIs, Korean Dietary Reference Intakes; KM, Korean Medicine; KNHANES, Korean National Health and Nutrition Examinations Survey; MetS, metabolic diseases; NAFLD, nonalcoholic fatty liver disease; OR, odds ratio; PR, prevalence ratio; SD, standard deviation; SFA, saturated fatty acid; SO, sarcopenic obesity; T2DM, type 2 diabetes; TG, triglycerides. balanced diet rich in vegetables, fruits, legumes, and fish is associated with a lower 10-year risk of incidence of CVDs than the typical white rice and grain-based Korean diet in elderly people (20). The recent Korean National Health and Nutrition Examinations Survey (KNHANES) reported that excessive carbohydrate, low fruit, and imbalanced food and nutrient intakes contribute to cardiometabolic abnormalities in rural residents (21).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, poor diet accounted for 11% of disability-adjusted life-years lost and 529,299 deaths in the United States, with 83.9% of these deaths caused by cardiovascular diseases (US Burden of Disease Collaborators, 2018). It also has a great impact on older adults’ health; previous studies have reported that older adults with poor, unhealthy diet, such as a low quality diet and a high cholesterol intake, were more likely to develop chronic diseases and have a higher mortality risk than those with healthy diet (Houston et al, 2011; Hsiao et al, 2013; Lagström et al, 2020; Reedy et al, 2014; Seo & Hwang, 2021; Xu et al, 2014). While much existing research has focused on major chronic diseases and mortality as health outcomes, there is a growing interest in using biomarkers to understand a complex relationship between diet, nutrition, and health (Picó et al, 2019).…”
Section: Introductionmentioning
confidence: 99%